Gestión de procesos logísticos en el Comercial Escobar de la ciudad de Vinces en el periodo 2023. - Villamar Güillín, Jennyfer Carolina (2024)
This case study aims to analyze the logistics process management at Comercial Escobar in the city of Vinces during 2023, with the objective of improving product supply efficiency. Issues identified include the lack of a reliable inventory control system, inefficiencies in purchase planning, and insufficient staff training. The applied methodology included analytical, deductive, bibliographic, and descriptive methods, along with employee surveys and an interview with the store manager. The results indicate that the company faces both stock shortages and overstocking, as well as a lack of staff training in inventory and logistics management. Additionally, it was found that inefficient logistics management negatively impacts the store’s profitability and competitiveness. It is recommended to implement technological tools for more precise stock control, adopt methodologies based on historical data analysis and real demand, and develop staff training programs in logistics processes.